2003
DOI: 10.1097/00004770-200309000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Apical Transportation in Four Ni-Ti Rotary Instrumentation Techniques

Abstract: A new radiographic technique was used to compare apical transportation in four Ni-Ti rotary instrumentation sequences. Mesiobuccal canals of 60 extracted mandibular molars were randomly divided into four groups. Groups 1 and 3 were instrumented by crown-down and groups 2 and 4 by step-back technique with 0.06 ProFiles series 29 to size 6. In groups 3 and 4 Greater Taper files were first used in a crown-down manner. The central axes of initial and final instruments were radiographically superimposed to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 17 publications
4
58
0
6
Order By: Relevance
“…Some studies evaluating the shaping of the root canals by micro-CT (9, 15-17) have been published, which show that it is a non-invasive method that accurately reproduces the three-dimensional internal and external tooth morphology, allowing the superimposition of renderings of the preoperative and postoperative canal system with high resolution (9). Nevertheless, the radiographic method has been used by several researchers to assess root canal curvature (6,10,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies evaluating the shaping of the root canals by micro-CT (9, 15-17) have been published, which show that it is a non-invasive method that accurately reproduces the three-dimensional internal and external tooth morphology, allowing the superimposition of renderings of the preoperative and postoperative canal system with high resolution (9). Nevertheless, the radiographic method has been used by several researchers to assess root canal curvature (6,10,18).…”
Section: Discussionmentioning
confidence: 99%
“…Only roots with radiographic confirmation of Vertucci's type IV root canal configuration in the mesiobuccal root were selected. All the roots were immersed in alginate, and a series of radiographs were taken through a collimator placed on a marked platform, to determine the location of the root's greatest curvature (10) and the radius. Their angle of curvature was determined as described by Pruett et al (1) using AutoCAD 2008 (Autodesk Inc, San Rafael, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The use of high-resolution computed tomography (micro-CT) to study root canal anatomy is a promising tool, but there are few difficulties that need to be overcome concerning the structure of tomographic experiments and the reconstruction and analysis of the 3D data configuration obtained. 12,[17][18][19] Furthermore, micro-CT scans can only detect the inorganic aspects of accumulated debris and not the organic counterparts. 20,21 In the present study, the setup combined with digital images and use of computer software enabled precise evaluation of even minor changes in the canal geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Shaping the root canal system with a greater taper and larger apical foramen size are recommended, likely to remove more of the infected dentin and create space for the irrigants and antibacterial medicaments to eradicate bacteria 2) . Therefore, various nickel-titanium (NiTi) rotary and reciprocating files with a greater taper and larger apical diameter were developed 3) . Recent studies have shown that NiTi rotary and reciprocating files greatly improved the clinical outcomes and reduced the incidence of preparation errors 4) .…”
Section: Introductionmentioning
confidence: 99%